2008
DOI: 10.1159/000129678
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormones and Their Relation to Weight Status

Abstract: Background/Aims: The aim of this study was to analyze thyroid hormones in female adolescents with obesity and anorexia nervosa (AN) before and after normalization of weight. Methods: Thyroid-stimulating hormone (TSH), fT3, and fT4 were determined in 100 obese girls, 32 normal-weight girls and 20 girls with AN aged 14–18 years at baseline and 1 year later. Additionally, leptin, insulin, and the insulin resistance index HOMA were analyzed in the obese and normal-weight girls. Results: TSH and fT3 levels of girls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
132
3
13

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 161 publications
(175 citation statements)
references
References 68 publications
(57 reference statements)
24
132
3
13
Order By: Relevance
“…Contrasting results were reported by other authors who did not detect any association between TSH levels and HOMA-IR (5,14).…”
Section: δBmc-sdscontrasting
confidence: 99%
See 4 more Smart Citations
“…Contrasting results were reported by other authors who did not detect any association between TSH levels and HOMA-IR (5,14).…”
Section: δBmc-sdscontrasting
confidence: 99%
“…Leptin stimulates TSH production acting through the hypothalamic-pituitary axis (3,9,17). It has been recently reported that leptin signaling, mediated by JAK/STAT pathway, is mandatory for the maintenance of TRH expression in the hypothalamic paraventricular nucleus and thus, for normal production of TSH and thyroid hormones (9,11,14,17,28). This finding is corroborated by our results, as our obese patients with hyperthyrotropinemia showed significantly higher fT3 values.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations